Numerical simulation to study effect of die design parameters on deformation possibility of metal on combined drawing - Tien, Nguyen Manh; Hoan, Tran Duc; An, Nguyen Truong; Tuan, Pham Manh (Vietnam Journal of Science and Technology, 2018)
This paper uses numerical simulation to study amethod in combined drawing process with thinning the wall when drawing of a cylindrical cup of sheet metal. The software Deform 2D is used to examineeffect of die design parameters (inclination of die) on deformation possibility of metal. Simulation results in order to select appropriate die design parameters (conical die), to enhance the ability to deform and contribute to improve product quality.